Pemanfaatan Aplikasi TikTok pada Pembelajaran Teks Negosiasi Kelas X SMA Negeri 11 Semarang - Titis Ardyasti; Hana SilmaHadana; Nurus Sa’adah; Asep Purwo Yudi Utomo; Ngabiyanto Ngabiyanto; Nur Rakhmat; Indah Sukawati (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Educating the nation's life is one of the goals of the Indonesian state which is included in the Preamble to the 1945 Constitution of the Republic of Indonesia in the fourth paragraph. Through education, everyone can learn to develop their potential to realize their happiness and perfection in life to become more qualified. Learning Indonesian has an important role in the process of teaching students about good and correct Indonesian language skills according to their goals and functions. The use of the TikTok application is one way to integrate technology in learning in class X SMA Negeri 11 Semarang negotiation text material. This study aims to find out whether the TikTok application can be used as an alternative learning medium that is effective in improving language skills and increasing students' interest in learning. This research also aims to motivate educators to create interesting learning media. This research uses qualitative descriptive method. Its data collection techniques use observation, interviews, and documentation. The results of the use of the TikTok application in learning negotiation texts with the research objects of class X students of SMA Negeri 11 Semarang can be well received. Monotonous and boring learning can be resolved using TikTok media